A case control study to elicit fetal outcome in high-risk pregnancies and to study the various maternal parameters associated with fetal outcomes - Parmar, Jyoti; Jain, Sheela; Singh, Punya Pratap (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: High risk pregnancies (HRP) threaten the health or life of the mother or her fetus. Perinatal mortality varies widely in some developed countries and more than 10 times higher in developing countries. For most women, early and regular prenatal care promotes a healthy pregnancy and delivery without complication. Methods: It is a prospective study conducted in BMC, Sagar of duration one year, keeping in mind the inclusion and exclusion criteria with 216 (108 control and 108 cases) patients included in our study. Results: study shows that there is a significantly high incidence of IUGR delivery and preterm delivery in HRP as compared to control. Conclusions: In our study we conclude that there is a high correlation between HRP and poor perinatal outcome thus identifying HRP is important because it is the first step towards prevention perinatal mortality and morbidity.